Histone deacetylase 8 promotes innate antiviral immunity through deacetylation of RIG-I - Zhang, Huijun; Liu, Tingli; Liu, Xinhua; You, Fenfen; Yang, Jiaheng; Zhang, Nan; Huang, Ying; Liang, Gaofeng (Frontiers in Cellular and Infection Microbiology, 2024)
Histone deacetylates family proteins have been studied for their function in regulating viral replication by deacetylating non-histone proteins. RIG-Ⅰ (Retinoic acid-inducible gene Ⅰ) is a critical protein in RNA virus-induced innate antiviral signaling pathways.Our previous research showed that HDAC8 (histone deacetylase 8) involved in innate antiviral immune response, but the underlying mechanism during virus infection is still unclear. In this study, we showed that HDAC8 was involved in the regulation of vesicular stomatitis virus (VSV) replication. Over-expression of HDAC8 inhibited while knockdown promoted VSV replication. Further exploration demonstrated that HDAC8 interacted with and deacetylated RIG-I, which eventually lead to enhance innate antiviral immune response. Collectively, our data clearly demonstrated that HDAC8 inhibited VSV replication by promoting RIG-I mediated interferon production and downstream signaling pathway.